2010
DOI: 10.1007/s11262-010-0468-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of an isolate obtained from potato in 1985 revealed potato virus X was introduced to China via multiple events

Abstract: Potato virus X (PVX) is one of the most common plant viruses that cause great economic losses to solanaceous plants. We have previously reported the complete genomic sequence of the 2006 Chinese potato isolate FX21 and demonstrated that PVX isolates cluster into two groups: Eurasia and America. Here, we present the complete genomic sequence of one PVX isolate collected from potato in 1985 (PVX-1985). The genome of PVX-1985 is identical to that of FX21 in length and has the same genomic structure. PVX-1985, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…According to the results of this study and those of Yu et al [25,26] different selection pressure is operating on different genes of PVX, and the ORF encoding RdRp is under the highest selection pressure. Therefore, the RdRp ORF of 27 PVX complete genome were further divided into three parts as described by Yu et al [26] and their dN/dS values separately were calculated. Unlike previous studies by Yu et al, 2010 our results indicated the dN/dS values for three parts of genome were \1, despite the fact that RdRp-B was higher than RdRp-A and RdRp-C.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…According to the results of this study and those of Yu et al [25,26] different selection pressure is operating on different genes of PVX, and the ORF encoding RdRp is under the highest selection pressure. Therefore, the RdRp ORF of 27 PVX complete genome were further divided into three parts as described by Yu et al [26] and their dN/dS values separately were calculated. Unlike previous studies by Yu et al, 2010 our results indicated the dN/dS values for three parts of genome were \1, despite the fact that RdRp-B was higher than RdRp-A and RdRp-C.…”
Section: Discussionsupporting
confidence: 56%
“…The Iranian isolates are part of clade I with clade II representing isolates from South America. Interestingly, the two isolates (PVX 2.7 and PVX 2.7b) from U.S.A are part of clade I and hence clearly indicates that the isolates from North America are distinct from those in the southern America contradicting the previous suggestion of two distinct lineages of PVX, Eurasia and America [3,13,25,26].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies have shown that the PVX isolates can be classified into two lineages, Eurasia and America, which correspond to their geographical origin [22,24,44,45]. PVX is well-known as a model for understanding pathogen-host interaction [4,14,20] and efforts in recent years have established good knowledge about genetic basis of resistance and the genetic system controlling behavior of the pathogen [2,21,32].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies on phylogenetic analysis, selection pressure operating on different genes, and estimation of genetic variability on different coding regions of PVX [24,44,45], there still remained a lack of information on evolutionary constraints for the two virus lineages, molecular diversity patterns, population differentiation and recombination event(s). Here, population genetic analysis of PVX isolates from different countries was done based on the CP sequences because conserved nature of the CP gene makes it a suitable candidate for such studies.…”
Section: Introductionmentioning
confidence: 99%